Pemanfaatan Herbal Daun Teh untuk Produk Sabun Cuci Piring di SMK Muhammadiyah Mlati - Siti Fatimah Sultan; Metty Hartanti; Dwi Utami (Jurnal Ilmiah Pangabdhi, 2025)
SMK Muhammadiyah Mlati is one of the vocational schools, especially pharmaceutical interest, located in Mlati sub-district, Sleman Regency, Yogyakarta Province. One of the natural products in Sleman district is tea leaves (Camellia sinensis). This activity can increase the knowledge and awareness of SMK Muhammadiyah Mlati students in applying the making of dish soap from tea leaves, one of which is by making a good and correct way. The purpose of this program is to provide knowledge and training on making dish soap from tea leaves to help reduce the community's need for soap at an affordable price. The methods used in this service program are (1) Preparation stage for making dish soap from tea leaves; (2) Training Stage for making dish soap from tea leaves; (3) Implementation and Practice Stage of making dish soap from tea leaves; (4) Evaluation Stage of making dish soap from tea leaves. The results of the activity show that the activities of this empowerment program are very enthusiastic and play an active role in participating in community service activities. Pharmacy students of SMK Muhammadiyah Mlati followed all activities well starting from the preparation, training, implementation, practice, to the evaluation stage. Thus, this learning approach does not only provide theoretical knowledge but also prepares students to enter the world of work with practical skills that are in accordance with industry demands.